Influencing Factors of Psychological Well-Being of the Non-designated Hospital Staff in China During the COVID-19 Pandemic - Yao, Dandan; Lyu, Jihui; Ma, Zongjuan; Champ, Mei; Xiong, Qian; Li, Mo; Li, Wenjie; Mu, Haiyan; Hu, Yueqing; Gao, Wenchao; Jia, Dongmei (Frontiers in Psychiatry, 2021)
Background: Recent studies report that hospital staff at the forefront of caring for COVID-19 patients experience increased psychological distress. To effectively manage the outbreak of COVID-19, China established COVID-19 designated and non-designated hospitals. To date, few studies have examined the impacts of COVID-19 on psychological health of staff working at non-designated hospitals. This study is to explore factors affecting psychological health of non-designated hospital staff in China during the COVID-19 pandemic. Methods: Data were collected through an online questionnaire between February and March 2020. The questionnaire consists of General Health Questionnaire (GHQ-20), Social Support Rating Scale (SSRS), Simplified Coping Style Questionnaire (SCSQ), sociodemographic characteristics, employment history, health status, and contact history of COVID-19. The questionnaire was distributed through hospital WeChat groups and work colleague referrals. A total of 470 non-designated hospital staff members completed the questionnaire. Multiple Linear Regression analysis was used to interpret the associations among social support, coping styles, sociodemographic factors, job roles, and psychological status. Data were analyzed using SPSS version 21.0. Results: The non-designated hospital staff differed significantly in anxiety and depression subscores of the GHQ-20 by their job roles, levels of social support, and history of mental disorders. Staff with medical job roles, good self-reported health status, no previous mental disorders, adequate social support, and positive coping styles scored lower in GHQ-20 total score, which indicated healthier psychological status. Conclusions: The results indicate that history of mental health disorders, non-medical job roles, and inadequate social support are associated with greater psychological distress. Personalized support should be provided to those who are vulnerable and in need of social and psychological support.